2023
DOI: 10.1108/ijem-07-2022-0274
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive leadership and job satisfaction in Omani higher education: the mediation of psychological ownership and employee thriving

Abstract: PurposeThrough the lens of social exchange and self-determination theories, this paper proposes and tests a model to explore how inclusive leadership practices foster employee job satisfaction at higher education institutions. It also explores the intervening roles of psychological ownership and employee thriving in this relationship.Design/methodology/approachThis study followed a positivist worldview and a quantitative methodology. The authors collected data from a sample of 329 academic and nonacademic staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…To develop a comprehensive conceptual model that describes the interactions between diversity, inclusion, employee retention, and job satisfaction, we can draw insights from several key references. Dahleez et al (2023) propose a model that links inclusive leadership to employees' job satisfaction through the mediating mechanisms of thriving at work and psychological ownership. This suggests that inclusive leadership plays a crucial role in influencing job satisfaction.…”
Section: A Conceptual Model That Describes the Interactions Between T...mentioning
confidence: 99%
“…To develop a comprehensive conceptual model that describes the interactions between diversity, inclusion, employee retention, and job satisfaction, we can draw insights from several key references. Dahleez et al (2023) propose a model that links inclusive leadership to employees' job satisfaction through the mediating mechanisms of thriving at work and psychological ownership. This suggests that inclusive leadership plays a crucial role in influencing job satisfaction.…”
Section: A Conceptual Model That Describes the Interactions Between T...mentioning
confidence: 99%
“…Inclusive leaders provide a supportive and safe environment in which employees can voice their opinions. Research has demonstrated various positive outcomes arising from inclusive leadership such as happiness at work (Jha et al, 2023), structural empowerment (Lu et al, 2023), green innovative service behavior (Asghar et al, 2023), meaningful work (Shafaei & Nejati, 2023), organizational identification (Naseer et al, 2023), thriving at work (Dahleez et al, 2023), and resilience capacity (Gong et al, 2023), to name a few.…”
Section: Inclusive Leadership and Wbmentioning
confidence: 99%